USING PROCESS-ORIENTED STRATEGIES IN THE CLASS TO MAKE ESL LEARNING POSSIBLE - Farzana Sohail (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2017)
English teachers from time to time have been trying multiple methodologies to teach ESL. They are ranged as Grammar Translation Method,The Direct Method, The Audio-Lingual Method, The Silent Way, Desuggestopedia, Community Language Learning, Total Physical Response, Communicative Language Teaching, Content-based to Task-based, and Participatory Approaches. Thesemethodologies are based on both teacher centered approach and student centered approach. LarsenFreeman views that methods serve as a foil for reflection that can aid teachers in bringing to conscious awareness the thinking that underlie their actions and also they are able to see why they are attracted to certain methods and repelled by others. But if we look into the outcome of the learning we feel and notice that the learning is not validated by these pedagogies and the learners are left to uncertain situation and are not sure whether they would ever learn ESL and use it in their daily life situations, perfectly and according to the context. This paper aims to discuss those strategies which the researcher has been using in her classrooms for past few years and found valid and outcomebased. These class based methodologies have been termed as Process-oriented Strategies, are discussed in the paper and the outcomes are shown as to how the students actually learnt ESL and are effectively using that in their daily lives. To consolidate these approaches, a sample of twenty learners was randomly selected for this study to assess the outcome of the learning of ESL. The learner centered approach was adopted throughout the session. The result showed that through process-oriented methods learners were able to use English in their daily lives very effectively and spontaneously.